2017
DOI: 10.1074/jbc.r117.787101
|View full text |Cite
|
Sign up to set email alerts
|

Iron–sulfur cluster biogenesis and trafficking in mitochondria

Abstract: The biogenesis of iron-sulfur (Fe/S) proteins in eukaryotes is a multistage, multicompartment process that is essential for a broad range of cellular functions, including genome maintenance, protein translation, energy conversion, and the antiviral response. Genetic and cell biological studies over almost 2 decades have revealed some 30 proteins involved in the synthesis of cellular [2Fe-2S] and [4Fe-4S] clusters and their incorporation into numerous apoproteins. Mechanistic aspects of Fe/S protein biogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
293
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(304 citation statements)
references
References 100 publications
0
293
0
Order By: Relevance
“…11 Once iron is taken up by the cell, iron can be targeted to the mitochondria for heme and iron-sulfur cluster biosynthesis. 1215 Within the mitochondrion, the metabolic processes associated with iron uptake and hematopoiesis are interdependent and facilitated by a network of enzymes, including δ-aminolevulinic acid-synthase (ALAS, EC 2.3.1.37) and ferrochelatase (FECH, EC 4.99.1.1). Recently, novel mechanisms associated with iron uptake and heme metabolism have been identified, which can further our understanding of the biochemical properties of erythroid development.…”
Section: Iron In Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…11 Once iron is taken up by the cell, iron can be targeted to the mitochondria for heme and iron-sulfur cluster biosynthesis. 1215 Within the mitochondrion, the metabolic processes associated with iron uptake and hematopoiesis are interdependent and facilitated by a network of enzymes, including δ-aminolevulinic acid-synthase (ALAS, EC 2.3.1.37) and ferrochelatase (FECH, EC 4.99.1.1). Recently, novel mechanisms associated with iron uptake and heme metabolism have been identified, which can further our understanding of the biochemical properties of erythroid development.…”
Section: Iron In Biologymentioning
confidence: 99%
“…1215 Iron that is not utilized for heme or iron-sulfur cluster assembly is stored within mitochondrial ferritin (mitoferritin). 52 Both cytosolic ferritin 53 and mitoferritin 54 mediated mineralization of iron minimize the production of potentially harmful hydrogen peroxide.…”
Section: Mitochondrial Iron Metabolismmentioning
confidence: 99%
“…The maturation and insertion of [Fe–S] clusters into apo-target proteins require mitochondrial ISC assembly machinery that contains scaffold protein IscU, cysteine desulfurase (Nfs1), accessory protein Isd11, activator/iron donor Frataxin, and Ferredoxin (Agar et al, 2000; Colin et al, 2013; Cory et al, 2017; Johnson et al, 2005; Lill, 2009; Pandey et al, 2013; Raulfs, O’Carroll, Santos Dos, Unciuleac, & Dean, 2008; Schmucker et al, 2011; Tsai & Barondeau, 2010; Webert et al, 2014; Yoon & Cowan, 2003; Zheng, Cash, Flint, & Dean, 1998). [Fe–S] clusters are assembled in mitochondrial and cytosolic machineries (Braymer & Lill, 2017; Bridwell-Rabb, Fox, Tsai, Winn, & Barondeau, 2014; Lill et al, 2006), and clusters are transferred to apo-target proteins aided by chaperones HscA/HscB upon maturation (Bonomi, Iametti, Morleo, Ta, & Vickery, 2011; Chandramouli & Johnson, 2006; Fox, Chakrabarti, McCormick, Lindahl, & Barondeau, 2015; Fox, Das, Chakrabarti, Lindahl, & Barondeau, 2015; Uzarska, Dutkiewicz, Freibert, Lill, & Muhlenhoff, 2013; Vranish et al, 2015). Defects in Fe–S cluster assembly and maturation lead to multiple human diseases and protein dysfunctions (Rouault, 2015; Stehling, Wilbrecht, & Lill, 2014) that encompass many processes including metabolism, DNA maintenance, Fe–S cluster assembly machineries, respiratory chain metabolism, ribosome function, and tRNA modification (Andreini, Banci, & Rosato, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In eukaryotic cells, ISC is synthesized in mitochondria and cytosol, although the de novo synthesis of ISC is initiated only in mitochondria [12]. It was suggested that approximately 30 proteins are involved in the machinery [13]. In human mitochondria, proteins including ISCU, NFU, ISCA and GLRX5 provide the scaffold for assembling the ISC; the complex of ISCS and ISD11 supplies sulfur; and frataxin (FXN) might provide the iron for initial ISC formation [14].…”
Section: The Role Of the Iron-sulfur Cluster And Its Biogenesis In Ermentioning
confidence: 99%